Financial Analysis Of Laying Duck On People's Farms In Pantai Labu District, Deli Serdang Regency - A. H. Daulay; E. Mirwandhono; Ramayani, M.D (Talenta Publisher, 2021)
Business productivity at the farm level is still low when compared to commercial businesses both in terms of business management, quality and quantity of production.This study aims to analyze financial aspects of laying ducks on community farms. The research was conducted in Pantai Labu District, Deli SerdangÂ Regency in November until October 2021. The samples were determined by stratified sampling, namely dividing three business scales based on the number of livestock ownership, i.e small-scale business (300-500 ducks), medium scale business (800 ducks) and the highest scale business(3.000-10.000 ducks) with the number of respondents per business scale of 3 breeders. Parameters were production cost, income. revenue, R/C, BEP, Net B/C, Gross B/C, NPV, IRR, and PP. Â The results of the study showed that the average income per period per business scale was Rp. 104.736.666, - Rp. 170.320.457, - and Rp. 1.606.308.080.Â R/C value> 1, the value of BEP production is smaller than the amount of egg production, BEP price is smaller than the selling price of eggs per egg, the value of Net B/C and Gross B/C> 1, the NPV value> 0 or positive, the IRR value with an interest rate of 16.75%, respectively, is 55%, 50% and 55% greater than the interest rate and PP, respectively 10,15,8 months.